2022
DOI: 10.1186/s40659-022-00408-z
|View full text |Cite
|
Sign up to set email alerts
|

Auricular cartilage regeneration using different types of mesenchymal stem cells in rabbits

Abstract: Background Cartilaginous disorders comprise a wide range of diseases that affect normal joint movement, ear and nose shape; and they have great social and economic impact. Mesenchymal stem cells (MSCs) provide a promising regeneration alternative for treatment of degenerative cartilaginous disorders. This study aimed to compare therapeutic potential of different types of laser activated MSCs to promote auricular cartilage regeneration. Twelve adult rabbit allocated equally in four groups, all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Previous studies have found that HA can enhance the synthesis of cartilage ECM in vitro [63,64]. Similarly, MSCs can also promote chondrogenic differentiation of cells by updating ECM and synthesizing COL II [65]. Amann et al (2017) reported that in the process of differentiation of AMSCs, HA promoted chondrogenesis by upregulating the expression of GAG and prevented hypertrophy by downregulating the expression of COL X [66].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have found that HA can enhance the synthesis of cartilage ECM in vitro [63,64]. Similarly, MSCs can also promote chondrogenic differentiation of cells by updating ECM and synthesizing COL II [65]. Amann et al (2017) reported that in the process of differentiation of AMSCs, HA promoted chondrogenesis by upregulating the expression of GAG and prevented hypertrophy by downregulating the expression of COL X [66].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found that HA can enhance the synthesis of cartilage ECM in vitro [63, 64]. Similarly, MSCs can also promote chondrogenic differentiation of cells by updating ECM and synthesizing COL II [65]. Amann et al.…”
Section: Discussionmentioning
confidence: 99%
“…The different differentiation media were changed every 3 days for 21 days, and then the cells were washed and fixed in 10% formalin for 20 min and stained with Oil Red O solution in 10% isopropanol, Safranin-O staining, and Alizarin red for 15 min to assess adipogenic, chondrogenic, and osteogenic differentiation, respectively 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Although MSCs were observed to differentiate into auricular cartilage in the defective area of the ear in animal models, different kinds of MSCs also presented different capacities of chondrogenesis. In comparison, the researchers demonstrated that BMMSCs were superior to other stem cells in differentiation capacity (Chen et al, 2015;Oh et al, 2018;Hassan et al, 2022). BMMSCs are a representative cell source that promotes wound healing in multiple ways and develops into effector cells involved in angiogenesis, ECM formation, wound contraction, re-epithelialization, and matrix secretion (Hassan et al, 2022).…”
Section: Stem Cell Differentiation Methodsmentioning
confidence: 99%